Dolutegravir induces FOLR1 expression during brain organoid development - Caiaffa, Carlo Donato; Tukeman, Gabriel; Delgado, Christian Zevallos; Ambekar, Yogeshwari S.; Mekonnen, Taye T.; Singh, Manmohan; Rodriguez, Victoria; Ricco, Emily; Kraushaar, Daniel; Aglyamov, Salavat R.; Scarcelli, Giuliano; Larin, Kirill V.; et al. (Frontiers in Molecular Neuroscience, 2024)
During the first month of pregnancy, the brain and spinal cord are formed through a process called neurulation. However, this process can be altered by low serum levels of folic acid, environmental factors, or genetic predispositions. In 2018, a surveillance study in Botswana, a country with a high incidence of human immunodeficiency virus (HIV) and lacking mandatory food folate fortification programs, found that newborns whose mothers were taking dolutegravir (DTG) during the first trimester of pregnancy had an increased risk of neural tube defects (NTDs). As a result, the World Health Organization and the U.S. Food and Drug Administration have issued guidelines emphasizing the potential risks associated with the use of DTG-based antiretroviral therapies during pregnancy. To elucidate the potential mechanisms underlying the DTG-induced NTDs, we sought to assess the potential neurotoxicity of DTG in stem cell-derived brain organoids. The gene expression of brain organoids developed in the presence of DTG was analyzed by RNA sequencing, Optical Coherence Tomography (OCT), Optical Coherence Elastography (OCE), and Brillouin microscopy. The sequencing data shows that DTG induces the expression of the folate receptor (FOLR1) and modifies the expression of genes required for neurogenesis. The Brillouin frequency shift observed at the surface of DTG-exposed brain organoids indicates an increase in superficial tissue stiffness. In contrast, reverberant OCE measurements indicate decreased organoid volumes and internal stiffness.